PENINGKATAN MOTIVASI BERPRESTASI GURU MELALUI SUPERVISE AKADEMIK SD RAYON VI KECAMATAN TAMBANG KABUPATEN KAMPAR - Yusmarni ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The purpose of this study was to determine whether a teacher Achievement motivation can beenhanced through academic supervision in elementary Rayon VI Mining District of Kamparregency. The study was designed in two cycles, each cycle consisting of planning,implementation, observation, reflection and revision. Actions taken is supervision, followedby billing commitment and guidance. Data collection method used is observation. Averagedata analysis methods used is descriptive method. From the description of data processingand discussion it was concluded as follows: Aspects of academic supervision performed bytutor known that from the first cycle increased in the second cycle. If the first cycle to get ascore of 28, then on the second cycle has been getting better with the acquisition of a score of43. In the aspect of achievement motivation of teachers obtained in the first cycle of 60.1%with good dukup category and the second cycle increased to 81.6% with very goodcategories.